Low Energy Consumption in Chlor-alkali Cells Using Oxygen Reduction Electrodes - Yohannes Kiros and Martin Bursell (International Journal of Electrochemical Science)
An air/oxygen gas diffusion electrode for use as a cathode to replace the traditional hydrogen-evolving electrode in chlor-alkali electrolysis was assessed. Attempts to stabilize the cathode have been addressed in order to circumscribe problems associated with “flooding” or “wetting-in” properties. Variation of the hydrophobic concentration in the gas diffusion layer had a significant effect on the electrochemical tests of both the half-cell and electrolysis of the chlor-alkali cells. Life-tests as well as performance characteristics for both types of cells have shown encouraging results at NaOH concentration levels of ca 8M NaOH and temperatures of 70 and ca. 80 oC, respectively. Though cell voltages of about 2V were achieved and thereby reducing the energy consumption by 30-35% compared to the state-of-the-art membrane cell, the contributions of overvoltages were still high compared to the equilibrium potential of about 1.23V. Efforts to limit the individual parts of overvoltages as well as maintenance of the zero-gap cell at least on the anode side have been carried out. Two different kinds of cation exchange membranes have been used for the electrolysis cell. However, the cation exchange membrane with hydrophilic properties having high initial performances showed tendencies of blister formations.